2019
DOI: 10.18203/2394-6040.ijcmph20191808
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive study on sleep quality and its associated factors among elderly in urban population: Chidambaram

Abstract: Background: Population aging is a major health issue in most countries, sleep is one of the significant factors affecting aging and elderly people’s quality of life. The present study was done to assess sleep quality and its contributing factors among elderly people.Methods: This cross-sectional study was conducted in 2018 on 227 elderly people aged fifty five or more participants were selected from the urban field practice area Chidambaram. Data collection tools were a demographic questionnaire, pittsburg sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
1
6
1
Order By: Relevance
“…This observation is consistent with the findings of other studies done from India as well as China and Nigeria. (12,13,16,18) Our study observed that high BMI was not significantly associated with poor sleep which is similar to findings of Luo J et al from China. ( 16) However, studies by Shittu RO et al found that higher BMI was associated with poor sleep.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This observation is consistent with the findings of other studies done from India as well as China and Nigeria. (12,13,16,18) Our study observed that high BMI was not significantly associated with poor sleep which is similar to findings of Luo J et al from China. ( 16) However, studies by Shittu RO et al found that higher BMI was associated with poor sleep.…”
Section: Discussionsupporting
confidence: 89%
“…While our study findings showed that quality of sleep was not associated with any sociodemographic characteristics, several studies have shown that factors such as advancing age, female gender and being widowed to be associated with poor quality of sleep. (11)(12)(13)(15)(16)(17) Due to similar distribution of these background characteristics among the people with good and poor sleep, no difference was observed with respect to these parameters in our study.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…6 In another cross-sectional study conducted by Gouthaman et al revealed 65.2% of the elderly had poor sleep quality. 7 Similarly Thichumpa et al reported the prevalence of poor sleep quality as 44% among 266 community-dwelling elderly individuals in northern Thailand. 8 Similarly lower prevalence was also reported by Sagayadevan et al among the Singaporean elderly, Razali et al, Park et al in 157 Korean elderly, Wu et al in elderly of Taipei district, China and Tel in Turkey.…”
Section: Discussionmentioning
confidence: 96%
“…The current study also found that unmarried status was associated with an increased risk of poor sleep quality. Similarly, a study conducted in Chidambaram found that marital status was one of the most important factors resulting in different sleep quality 43. Furthermore, Das et al 44 found that unmarried individuals had a 5.01-fold higher risk of poor sleep quality (aOR 6.01, 95% CI 2.18 to 16.53).…”
Section: Discussionmentioning
confidence: 96%